SALURAN DAN EFISIENSI PEMASARAN TEMBAKAU VIRGINIA DI KABUPATEN LOMBOK TENGAH - Septiadi, Dudi; Nursan, Muhammad (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
The issue of price variability has become an interesting debate in the Virginia tobacco economic chain. The existence of marketing institutions in the Virginia tobacco economic chain, on the one hand, provides price certainty for farmers, on the other hand, if the marketing chain is longer, the distribution of profits obtained by farmers will be smaller. This research aims to analyze marketing channels and marketing efficiency of Virginia tobacco farming in Central Lombok Regency. The method used in this research is the descriptive method. Virginia tobacco marketing channel analysis uses a descriptive analysis approach, while Virginia tobacco marketing efficiency uses marketing margin, farmer's share and profit distribution analysis. The results of the research show that there are 2 types of marketing channels for Virginia tobacco in Central Lombok Regency, namely Marketing Channel I: Farmers - Collectors - Wholesalers; and Marketing Channel II: Farmers – Wholesalers. Marketing channels I and II of Virginia tobacco in Central Lombok Regency are declared to be efficient because the farmer's share value is 95% with a margin of IDR 2,333 and the profit distribution value is 1 in marketing channel I; and the farmer's share value is 100% in marketing channel II.. Keywords : Channels, Marketing, Tobacco, Virginia.